Rosacea – diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 2. Treatment - Anna Woźniacka; Joanna Czuwara; Dorota Krasowska; Ewa Chlebus; Grażyna Wąsik; Anna Wojas-Pelc; Lidia Rudnicka; Joanna Narbutt; Zygmunt Adamski; Rafał Czajkowski; Magdalena Czarnecka-Operacz; Iwona Flisiak; et al. (Przegląd Dermatologiczny, 2023)
Rosacea is a chronic inflammatory skin disease characterised by periods of remission and subsequent relapses typically provoked by environmental factors. Eruptions located on the face are easily visible and may be difficult to conceal, which leads to a decrease in patients’ self-esteem, quality of life, and general well-being. Since the aetiology of rosacea is multifactorial and not entirely understood, and the clinical characteristics and course of the disease are heterogeneous, therapy may be challenging. While a complete cure is not possible, in the majority of cases clinical improvement and long-term remission are satisfying both to the patient and physician. In recent years, the therapeutic approach has been significantly modified. Currently, the focus is placed on the need to personalise the treatment process and adapt it to the patients’ phenotypic characteristics. Combination therapies and new variants of existing topical and systemic drugs are increasingly being recommended. The mainstays of therapy are antiinflammatory agents. Proper skin care – along with the identification and avoidance of factors known to trigger consecutive episodes of rosacea – are also essential.